A survey and study of the aquatic fungi at Ton Nga Chang wildlife-sanctuary, Songkhla province - Jariya Sakayaroj (Prince of Songkla University, 2020)
Thesis (M.Sc., Microbiology)--Prince of Songkla University, 2000